2008
DOI: 10.2320/matertrans.mra2007261
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Forged Mg-Al-Zn-Ca Alloy

Abstract: Continuously-casted Mg-9Al-1Zn-1Ca (in mass%) alloy (Mg-Ca alloy) and Mg-9Al-1Zn alloys (Ca-free Mg alloy) were forged at 573 K and their mechanical properties were investigated by tension tests at ambient temperature and 573 K. The forged Mg-Ca alloy showed higher 0.2% proof stress than the forged Ca-free Mg alloy. The high strength for the Mg-Ca alloy was attributed not only to grain refinement by hot forging, but also to the strengthening mechanisms arising from the difference in thermal expansion and geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…The results showed that the Gibbs free-energy of Cu 6 Ce phase precipitation reaction increased with the rising of temperature, which indicated that lower temperature was beneficial to the precipitation of Cu 6 Ce phase. In the temperature range of calculation, the Gibbs free-energy values of Cu 6 Ce phase precipitation reaction are all less than zero, which means that the formation of Cu 6 Ce phase is feasible in thermodynamics.…”
Section: )mentioning
confidence: 74%
See 3 more Smart Citations
“…The results showed that the Gibbs free-energy of Cu 6 Ce phase precipitation reaction increased with the rising of temperature, which indicated that lower temperature was beneficial to the precipitation of Cu 6 Ce phase. In the temperature range of calculation, the Gibbs free-energy values of Cu 6 Ce phase precipitation reaction are all less than zero, which means that the formation of Cu 6 Ce phase is feasible in thermodynamics.…”
Section: )mentioning
confidence: 74%
“…1(b), it is clear that the values of S E are very small and it would not cause a large error if ignoring the values of S E in practical computation. From Cu-Ce binary phase diagram, 18) eight points between 1071 K and 1211 K were chosen to calculate the Gibbs freeenergy of Cu 6 Ce phase precipitation reaction. Figure 2 shows the relationships between ÁG ª and T for precipitation reactions of Cu 6 Ce in Cu-Ce binary alloy.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Chino et al 14) investigated microstructure and mechanical properties of the forged Mg alloy in which refined and homogeneous microstructure of pre-forging specimen provides good quality of the forged part. Hakamada et al 15) have tested mechanical properties of the forged MgCa alloy where the elongation increased largely since the stress concentration at second phase particles could be relaxed by diffusion. Matsumoto and Osakada 16) proposed a new concept of billet design to reduce the peak forging load in Mg forging, which were validated through finite element simulation and experiment using a servo-controlled press.…”
Section: )mentioning
confidence: 99%